BINYAH AL-KALIMÂT FÎ AL-LUGHATAIN AL-'ARABIYYAH WA AL-INDÛNÎSIYYAH WA WAZHÎFATUHÂ FÎ TA'LÎM AL-LUGHAH AL-'ARABIYYAH - Rafiatun Nazah Qomariah; Syaifuddin Ahmad Hussein; Faisal Mubarak (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This research aims to seek the equation and difference of establishment of words in two languages. Research method was contrastive analysis. The research found that: 1) aspects of the equation between the formation of the word/morphology in Arabic and Indonesia were located on af’âl in Arabic with verbs in Indonesian, isim and nouns and adjective. 2) aspects of the difference between the formation of the word/morphology in Arabic and Indonesia were verbs in Indonesian do not contain time meaning, meanwhile in Arabic mashdar does not only mean nouns but also the verb, isim fâ'il as adjective does not only mean subject/actor like isim maf’ûl, isim makân, alat and makân is similar to basic noun not derivative nouns. 3) the implications of contrastive analysis to the formation of the word/morphology in teaching Arabic is the foundation and facilitate the teacher in arranging teaching techniques, materials and the right learning methods.